1995
DOI: 10.1111/j.1432-1033.1995.tb20780.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Central and Peripheral Cannabinoid Receptors in Human Immune Tissues and Leukocyte Subpopulations

Abstract: Two proteins with seven transmembrane-spanning domains typical of guanosine-nucleotide-bindingprotein-coupled receptors have been identified as cannabinoid receptors ; the central cannabinoid receptor, CB1, and the peripheral cannabinoid receptor, CB2, initially described in rat brain and spleen, respectively. Here, we report the distribution patterns for both CB1 and CB2 transcripts in human immune cells and in several human tissues, as analysed using a highly sensitive and quantitative PCR-based method. CB1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
1,137
5
27

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,547 publications
(1,242 citation statements)
references
References 25 publications
39
1,137
5
27
Order By: Relevance
“…CB 2 receptor expression is restricted to the periphery, mainly in immune cells with particularly high levels in B cells and natural killer cells (Galiegue et al, 1995) although it has been reported that the CB 2 receptor is expressed in microglia cells of the CNS and in brain stem neuronal cells (Van Sickle et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…CB 2 receptor expression is restricted to the periphery, mainly in immune cells with particularly high levels in B cells and natural killer cells (Galiegue et al, 1995) although it has been reported that the CB 2 receptor is expressed in microglia cells of the CNS and in brain stem neuronal cells (Van Sickle et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…En effet, les effets psychotropes (euphorie, vertiges, anxiété, sédation, etc. ), ainsi que la dépendance au THC et autres composés addictogènes (nicotine, alcool, cocaïne), ont été essentiellement attribués au CB 1 R [13], alors que de nombreuses propriétés médicinales, en particulier celles liées à la modulation du système immunitaire, sont probablement associées au CB 2 R [14]. Le CB 1 R est abondamment exprimé dans le système nerveux central, et sa densité est particulièrement forte dans l'hippocampe, le cervelet et le striatum [15].…”
Section: Le Système Endocannabinoïdeunclassified
“…Le CB 1 R est abondamment exprimé dans le système nerveux central, et sa densité est particulièrement forte dans l'hippocampe, le cervelet et le striatum [15]. Le CB 2 R est présent également dans le système nerveux central [14], mais il est principalement exprimé sur les cellules immunes activées (lymphocytes B et T, macrophages, monocytes, cellules natural killer [NK], etc.) à des concentrations bien plus élevées que le CB 1 R [14].…”
Section: Le Système Endocannabinoïdeunclassified
“…Within mus, brainstem and bone marrow. Apart from expression in brain, the CB1 receptor is also expressed in the spleen, heart, prostate, uterus, ovary, thymus and testicles [61] . The location of CB2 receptor is more restricted, mainly at the peripheral level (the spleen, pharyngeal amygdales, B lymphocytes and to a lesser extent, monocytes and T lymphocytes) [61] .…”
Section: Target Receptorsmentioning
confidence: 99%
“…Apart from expression in brain, the CB1 receptor is also expressed in the spleen, heart, prostate, uterus, ovary, thymus and testicles [61] . The location of CB2 receptor is more restricted, mainly at the peripheral level (the spleen, pharyngeal amygdales, B lymphocytes and to a lesser extent, monocytes and T lymphocytes) [61] . Recently, CB2 expression has been demonstrated in activated microglia and also in neurons, but its level is lower than that of CB1 receptor [62][63][64][65] .…”
Section: Target Receptorsmentioning
confidence: 99%